The future of minorities in Syria - Sura Hussein Khader (Tikrit Journal For Political Science, 2025)
Syria's diverse ethnic demographics, including Assyrians, Armenians, Kurds, Christians, Druze, Ismailis, and Alawites, A major role in the system of government have played a significant role in shaping the country's future. However, on December 8 of last year, the scenario changed dramatically after Assad fled to Moscow and his regime collapsed The new government, led by the leader of Hayat Tahrir al-Sham, interim president Ahmad al-Sharaa, presents a new reality that is different from the previous regime, especially in the issue of minorities and their protection. Therefore, the issue of minorities was given special importance, and constituted the first major test for al-Sharaa in the political sphere. It is clear that protecting minorities in Syria is of paramount importance for establishing democracy in Syria, and the same is true for al-Sharaa and his government. Because his legitimacy inside Syria and on the international stage depends on it, and this is what we have observed in the Assad government, which derived its legitimacy by presenting an appearance of unity and cohesion among minorities in Syria. Therefore, we will go to extremes in this research on the future of minorities in Syria and compare between two stages: the stage of the Assad regime and the stage after the collapse of the Assad regime. We will use the historical method, the comparative method, and the method of future studies